GIS and remote sensing – desertification and progression of silting-up in the high plains of Oran in Western Algeria - Boukholkhal, Khadidja; Remaoun, Khadidja; Suiah, Sid Ahmed (Technium Social Sciences Journal, 2023)
The expansion of silting in the Algerian High Plains of south Oran (northwestern Algeria) is the ultimate manifestation of desertification. The presence, accumulation or deposition of sands in areas that previously did not contain any is the most visible sign of this silting up phenomenon that has begun to appear in recent decades. The present study focuses on the evolution and progression of silting up in the region under study. It is worth noting that assessing the narrowing of the vast endorheic depressions in this area is a very complicated task due to the vastness of the place. In order to deal with this problem in an efficient manner, it was deemed necessary to use remote sensing as it offers possibilities of global vision of the area to be studied and allows a precise description in time and space of this region. In order to efficiently identify and apprehend the phenomenon mentioned above, it was decided to adopt an analysis methodology that is based on the processing and interpretation of multi-date satellite images, combined with exogenous data. It should be noted that the topographic maps of Mecheria and Ain Sefra are given at a scale of 1/200,000 and are supplemented by some field data, along with some wind data. The analysis of data brought from different sources has made it possible to locate, characterize and map the evolution and the spatio-temporal dynamics of the recent extension of sandy accumulations, old Quaternary dune belts, and shrinking of vast endorheic depressions (Chott El Gharbi and Sebkhat Nâama). It is widely acknowledged that areas that are most affected by the progression of silting are the Plain of Naama, that is surrounded by the first Saharan Atlas ranges and by the orographic corridor formed by the double SW/NE alignment of Djebel (Mount) Morhad, Djebel Suigua, Djebel Aissa and Djebel Mekter located south of Ain Sefra. It is important to note that all this information, which is extracted from satellite images and exogenous data, will be integrated into a GIS.